A Corpus Analysis of Metadiscourse Markers Used in Argumentative Essays by Pakistani Undergraduate Students - Shafqat, Asmara (International Journal of Psychosocial Rehabilitation, 2020)
Metadiscourse is considered as one of the significant rhetorical features and strategies in the production of any piece of written or spoken discourse. It establishes a relationship of the writer with the audience in any communication process. The present study aimed at determining the frequency distribution of metadiscourse markers in argumentative essays of undergraduate students in a private sector university. This quantitative study adopted Hyland’s (2005) Interpersonal model of Metadiscourse.A corpus based software AntConc 3.5.7 was applied for a total of 124 argumentative essays. Finding of the study showed that the frequency of interactive metadiscourse markers was higher than interactional markers. It has also been observed that the most frequently used markers were transition markers whereas endophoric markers were used with less frequency. The results of the study have a few pedagogical implications. It highlights the importance of metadiscourse devices in learning and teaching writing skills in English Language Teaching (ELT) context and help to understand the norm of discourse markers. Moreover, metadiscourse analysis would benefit English language teachers to develop the writing skills of learners with appropriate use of metadiscourse devices.